2022
DOI: 10.3390/jpm12071098
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Embolization of Uterine Arteriovenous Malformation: A Systematic Review of Success Rate, Complications, and Posterior Pregnancy Outcomes

Abstract: Uterine Arteriovenous Malformation (UAVM) is a rare but life-threating cause of uterine bleeding. The clinical management of this condition is challenging, and there is a need to describe the most adequate approach for these patients. Uterine artery embolization (UAE) is the most widely-published treatment in the literature in recent years, although there is a need to update the evidence on this treatment and to compare it with other available therapies. Thus, the objective of this systematic review is to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…UVAs are rare, although the precise incidence is unknown due to heterogeneity in definitions and reporting bias in the literature, with the most recent systemic review by Ruiz Labarta et al identifying 371 cases of DSA-confirmed UVAs reported in the literature from 2000 to 2021. 1 2 3…”
Section: Definitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…UVAs are rare, although the precise incidence is unknown due to heterogeneity in definitions and reporting bias in the literature, with the most recent systemic review by Ruiz Labarta et al identifying 371 cases of DSA-confirmed UVAs reported in the literature from 2000 to 2021. 1 2 3…”
Section: Definitionsmentioning
confidence: 99%
“…UVAs can be categorized by general etiology of congenital versus acquired, with literature almost exclusively discussing the latter. 1 4 In practice and in the literature, there has been conflicting terminology, with “uterine arteriovenous malformation (AVM)” the prevailing, albeit technically inaccurate, term to describe all types of UVAs. 2 5 6 For this review, the term UVA is used to collectively describe hypervascular myometrial abnormalities, including true uterine AVMs, arteriovenous fistulas (AVFs), and non-AVM vascular anomalies, which Timmerman et al described as low-flow lesions without early filling of a draining vein.…”
Section: Definitionsmentioning
confidence: 99%
See 3 more Smart Citations